Medical liability claims in gynaecologic care: retrospective analysis of claims related to gynaecology in the Netherlands (2005-2022) - Is there a connection between treatment indication, phase of treatment and the risk of medical malpractice claims? - Désirée Klemann; Rankie ten Hoopen; Helen Mertens; Frits van Merode (BMC, 2024)
Abstract Background An increased interest in medical liability claims has been noticed. Nevertheless, detailed data on subject of claims and possible factors that contribute to litigation and indemnity payments are scarce and relatively dated. Insight into these data may provide valuable information to prevent both incidents and malpractice claims. Objective To analyse the subject, outcome and costs of malpractice claims related to gynaecological care and their connection with treatment indications and treatment phases. Design A retrospective analysis of malpractice claims related to gynaecology. Setting All claims related to gynaecology, filed and closed by Netherlands' largest liability insurance company, Centramed between 2005 and 2022. Sample N = 382. Methods An in-depth analysis of claim files was performed. Results A total of 68.6% of the claims were related to perioperative incidents. A total of 88.0% of all claims were related to treatments with a benign indication and only 12.0% were related to malignancies. The share of malignant treatment indications was high for claims related to diagnostic incidents (37.9%), compared to 7.3% for claims related to surgical treatment. Liability was accepted in 22.5% of all claims. The total costs of all claims amount €6,6mlj. Besides the indication for treatment, deficient expectation management (a lack of informed consent) contributes to dissatisfaction and increases the risk of malpractice claims. Finally, an inadequate medical file compromises legal defence and influences the judgement and settlement of malpractice claims. Conclusions There is a connection between treatment indications and treatment phases and the risk of malpractice claims and their outcome.